Collaborative teaching / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2023)
Collaborative teaching involves experts from within and across disciplines along with the industrial practitioners, working together to educate, mentor, facilitate and train groups of students with the aim to empower student self- learning. The collaboration is not only limited to Delivery but could also incorporate Content Development and Assessment. Having said that, on 22 May 2023, a collaborative teaching session was carried out in my ELC590 Oral Presentation class. The Delivery approach was selected. The invited guest lecturer was Ms Maria Leah Madumma Paula Estacio, a lecturer from the School of Education, Xavier University, the Philippines.